Effective Pre-Clinical Treatment of Fish Envenoming with Polyclonal Antiserum - Lopes Ferreira, Monica; Falcão, Maria Alice Pimentel; Bruni, Fernanda Miriane; Haddad, Vidal [UNESP]; Marques, Elineide Eugênio; Seibert, Carla Simone; Lima, Carla (MDPI, 2023)
Envenomation by venomous fish, although not always fatal, is capable of causing damage to homeostasis by activating the inflammatory process, with the formation of edema, excruciating pain, necrosis that is difficult to heal, as well as hemodynamic and cardiorespiratory changes. Despite the wide variety of pharmacological treatments used to manage acute symptoms, none are effective in controlling envenomation. Knowing the essential role of neutralizing polyclonal antibodies in the treatment of envenoming for other species, such as snakes, this work aimed to produce a polyclonal antiserum in mice and test its ability to neutralize the main toxic effects induced by the venoms of the main venomous Brazilian fish. We found that the antiserum recognizes the main toxins present in the different venoms of Thalassophryne nattereri, Scorpaena plumieri, Potamotrygon gr. Orbignyi, and Cathorops spixii and was effective in pre-incubation trials. In an independent test, the antiserum applied immediately to the topical application of T. nattereri, P. gr orbygnyi, and C. spixii venoms completely abolished the toxic effects on the microcirculation, preventing alterations such as arteriolar contraction, slowing of blood flow in postcapillary venules, venular stasis, myofibrillar hypercontraction, and increased leukocyte rolling and adherence. The edematogenic and nociceptive activities induced by these venoms were also neutralized by the immediate application of the antiserum. Importantly, the antiserum prevented the acute inflammatory response in the lungs induced by the S. plumieri venom. The success of antiserum containing neutralizing polyclonal antibodies in controlling the toxic effects induced by different venoms offers a new strategy for the treatment of fish envenomation in Brazil.
Keywords: Cathrops spixii; fish venom; neutralizing antibody; polyclonal antiserum; Potamotrygon gr orbignyi; Scorpaena plumieri; Thalassophryne nattereri; toxic effects